“IT IS EMOTION AND STRENGTH THAT WE ARE CONVEYING THROUGH MUSIC” - Adél FEKETE (Studia Universitatis Babeş-Bolyai. Musica)
Conductor Keri-Lynn Wilson began her musical studies at a very young age. While other children were still learning how to talk, she first started her piano lessons at the age of three, completing her passion for music by gradually adding two other instruments: the violin and the flute. The first major success of the young flautist was her Carnegie Hall debut at the age of 21. Soon a new passion arrose: conducting, under the guidance of Otto-Werner Mueller at The Juilliard School of Music in New York. As a student also had the opportunity of being the assistant of Claudio Abbado at the Salzburg Festival. Since then, Keri-Lynn Wilson has worked with famous symphony orchestras and opera houses all over the world, such as: Dallas Symphony Orchestra, Toronto Symphony, Los Angeles Philharmonic, Gewandhaus Orchestra, Simón Bolívar Symphony Orchestra, Vienna Staatsoper, Bolshoi Theatre, Arena di Verona, Israeli Opera. Returning to Cluj to once again conduct the great operatic masterpiece Tannhäuser, the maestra agreed to sit down for an interview focusing on about a conductor’s life and work in the XXI century, her unique musical thinking, current and future projects and on the experience of conducting in Romania.